Impact of Gluten-Free and Casein-Free Diet on Behavioural Outcomes and Quality of Life of Autistic Children and Adolescents: A Scoping Review - Kristina Zafirovski; Mirjana Trpevska Aleksoska; Joe Thomas; Fahad Hanna (MDPI AG, 2024)
Background: Gluten- and casein-containing foods could aggravate the symptoms of children and adolescents with autism spectrum disorder (ASD), and subsequently impact their quality of life. However, there is a mixed opinion among researchers concerning the impact of alternative diet on reducing ASD symptoms. Objective: This scoping review aimed at examining the impact of the "gluten-free, casein-free" (GFCF) diet on health outcomes and the quality of life among autistic children and adolescents. Methods: A scoping review of the literature was performed following the Joanna Briggs Institute (JBI) guidelines. Four databases, including EbscoHost, Medline, CINAHL, and ProQuest, were used to obtain subject-specific studies relevant to the research question and published between July 2013 and March 2024. A comprehensive search using keywords such as "autism spectrum disorder", "gluten-free diet", and "casein-free diet" was conducted to obtain articles related to the research focus area. Only full-text, peer-reviewed, written in English articles were selected. Data extraction and data analysis were performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-extension to Scoping Review (PRISMA-ScR) protocol. Results: From the initial 586 studies, a total of 27 articles were included in the final analysis of the review. The thematic analysis included "GFCF diet and improvement of the core autistic symptoms", "the gut-brain link", "dietary interventions and autism", "possible side effects due to the GCFC diet", and "inconclusive studies and mixed opinions". A majority of the studies showed a positive effect of the GFCF diet on a variety of autistic symptoms, including positive changes in cognitive skills, behaviour, and gastrointestinal symptoms, while some showed conflicting evidence. Conclusions: The currently available evidence on the impact of the "GFCF" diet on the quality of life of autistic children and adolescents may warrant potentially effective interventions for alleviating symptoms of autism spectrum disorders. However, this scoping review highlights the need for more research to provide more reliable evidence on the health outcomes and quality of life of ASD sufferers to guide practice.